Analysis of the Factors Influencing the Participation of Women's Papalele Fishermen to Improve the Family Economy - Merlin Chrisbel Sahertian; Maria Tupamahu; Jeanee Belthia Nikijuluw (Indonesian Journal of Global Health Research, 2023)
The husband’s limited income as a fisherman causes the wife to play a role in supporting the economic life of the household. Working as papalele is the choice of fisherman’s wives besides marketing the results of their husband’s response, this job is easier and quicker to generate income. The purpose of this study was to determine the factors the influence papalele fishing women to improve the family economy in the nusaniwe sub-District, Ambon City. The research method used is descriptive quanitative. The sampling technique for respondents in this study was random sampling. The number of samples from this study were 120 respondents (women papalele fishermen). This respondent represents another respondent who also works as a papalele. The sample calculation can use the Slovin formula, so the number of samples used in this study is 84,567 respondents rounded up to 85 respondents. Data collection techniques used in research are using questionnaires and interviews. Multiple linear regression analysis was used in this study. The results of the study obtained simultaneously the factors of education level, husband’s income and age have a significant effect on the role of fisherwomen in supporting the family economy in Nusaniwe District, Ambon City, while other factors, namely, education level, number of family dependents and age do not significantly influence the role of fisherwomen in supporting the family economy in the District Nusaniwe City of Ambon.